«<...> Я не желала жить в Советском Союзе, я желала жить в Германии и для этого предпринимала меры бежать в Германию <...>». Сторінки життя Юти Густавівни Кельм (Лідії Іванівни Кельман) - Нестеренко, Л. (Сiверянський лiтопис, 2019)
Статтю присвячено доньці німецького колоніста Густава Йогановича Кельма –
Юті Густавівні Кельм, яку в 1942 р. було вивезено з м. Прилуки на примусові роботи
до Німеччини, а в 1947 р., після її повернення назад до міста, засуджено до 10 років позбавлення волі. Після введення в дію Указу Президії Верховної Ради СРСР від 17 вересня
1955 р. «Про амністію радянських громадян, які співробітничали з окупантами в роки
Великої Вітчизняної війни 1941–1945 рр.» молоду жінку було звільнено та знято з неї
судимість. У 1991 р. її було реабілітовано. The article is devoted to the daughter of the German colonist Gustav Johannovych Kelm
named Yuta Gustavivna Kelm, who in 1942 at the age of sixteen was taken from Pryluky city
to Germany for forced labour. At first, the girl worked at a flax processing plant in Ohrdruf
town for the period from July 1942 to August 1944. After a fire that caused the factory to
stop, Yuta worked at «Olympia» factory in Erfurt, where typewriters were produced. Here
the girl was working on a German font. In April 1944 she got German citizenship.
In May 1945, after arrival of American forces to Erfurt, Yuta went to a collection and
transit center where she stayed for about 1.5-2 months. After the city became a part of the
Soviet Zone of Occupation, Yuta, obtaining a passport with new data in the name of Lidiia
Ivanivna Kelman, began to work as a freelance translator at the Army Grain Warehouse No.
3302 in Erfurt. Since October 1945, the girl worked at the buffet of the officers’ mess No. 29
of the Guards Corps of the Army Post Office No. 17995 «А”. In May 1946, she was transferred
to the post of supply manager of a junior secondary school in the same military unit.
In January 1946, the girl went through the first filtration in the city of Gotha. In September
1946, she went through the second filtration at the camp No. 363 in the town of D beln.
The filtration documents indicate her dual data, namely, the surname – Kelman/Kelm, the
name – Lidiia/Yuta, patronymic – Ivanivna/Gustavivna, and also it was recorded that the
girl collaborated with the Gestapo. In order to find her relatives, the girl came to Pryluky city
in October 1946.
In 1947, Yuta Gustavivna was sentenced to 10 years in prison. After the adoption of
the Decree of the Presidium of the USSR Supreme Soviet dated September 17, 1955 «On
amnesty of the Soviet citizens collaborating with occupants during the Great Patriotic War
1941–1945”, the young woman was released and her criminal record was canceled. She was
rehabilitated in 1991.